Measurement and valuation of the attributes of innovation of healthcare technologies: a systematic review. (31st December 2022) - Syeed, M. Sakil; Poudel, Nabin; Ngorsuraches, Surachat; Diaz, Jose; Chaiyakunapruk, Nathorn
Abstract: Objective: Innovative technologies (e.g. treatments) play a pivotal role in improving patient's well-being and in consequence population health outcomes. However, there is lack of consensus and comprehensive summary what constitutes innovation. Additionally, valuing them using traditional cost-effectiveness analysis is unlikely to capture the full range of benefits of these innovative technologies. This review aims to understand how innovation attributes were measured and/or valued in healthcare. Materials and methods: We systemically searched four databases, PubMed, Embase, PsycINFO, and Econlit, from inception to April 2021. Studies were included if they measured and/or valued the attributes of innovation for healthcare identified in our previous systematic review. Any other potential recommended methods to measure and/or value the innovation attributes were also extracted. Results: Of 546 articles, a total of 17 articles were finally included in this review. If attributes were measured and traded-off relative to costs, then it was considered as valuation of those attributes. Two specific attributes of innovation, i.e. substantial benefits and convenience and/or adherence were measured using adherence rate and life year or QALY gain. When innovation attribute was non-specific it was described as "overall innovation" and measured using overall innovativeness scale (e.g. point/binary scale). QALY-based cost-effectiveness analysis (CEA) was commonly used to assess and value substantial benefit attribute. Other valuation approaches were (i) rating, (ii) the economic value of life year gain, (iii) multiple criteria decision analysis (MCDA), (iv) incremental net health benefit (INHB), and (v) quality-adjusted cost of care (QACC). ICER threshold adjustment and multiple-criteria decision analysis (MCDA) are two common recommended approaches to capture the innovation comprehensively. We found that MCDA approaches often promoted and discussed but were sub-optimally used to incorporate different value attributes into decision-making. Conclusions: Existing methods used by payers to measure and value the innovation component of a new product do not reflect the full range of health and cost impacts. They generally do not consider the alternative perspectives of patients, providers, caregivers, and society. Key challenges remain to appropriately measure and value innovation attributes and incorporate them into HTA decision making.